2019
DOI: 10.1038/s41419-019-1727-6
|View full text |Cite
|
Sign up to set email alerts
|

Reduced P53 levels ameliorate neuromuscular junction loss without affecting motor neuron pathology in a mouse model of spinal muscular atrophy

Abstract: Spinal Muscular Atrophy (SMA) is a childhood motor neuron disease caused by mutations or deletions within the SMN1 gene. At endstages of disease there is profound loss of motor neurons, loss of axons within ventral roots and defects at the neuromuscular junctions (NMJ), as evidenced by pathological features such as pre-synaptic loss and swelling and post-synaptic shrinkage. Although these motor unit defects have been widely described, the time course and interdependancy of these aspects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 43 publications
3
28
3
Order By: Relevance
“…In accordance, the SMNΔ7 mouse model exhibits pronounced NMJ pathology predominantly in proximal muscles ( Kong et al, 2021 ; Ling et al., 2012 ; Ruiz et al., 2010 ) that reliably reflects the proximo-distal disease progression in patients with SMA ( Dubowitz, 2009 ). In contrast, the Taiwanese and Smn 2B/ - models exhibit only modest NMJ denervation ( Bowerman et al., 2012 ; Courtney et al, 2019b ; Lin et al., 2016 ). Moreover, while the degeneration and dysfunction of proprioceptive synapses onto motor neurons have been shown as one of the earliest pathological events in SMNΔ7 mice ( Fletcher et al., 2017 ; Mentis et al., 2011 ; Simon et al., 2019 ; Vukojicic et al., 2019 ), they have only been investigated at end-stage in the other two models ( Ackermann et al., 2013 ; Cervero et al., 2018 ; Hosseinibarkooie et al., 2016 ; Shorrock et al., 2018 ).…”
Section: Introductionmentioning
confidence: 89%
“…In accordance, the SMNΔ7 mouse model exhibits pronounced NMJ pathology predominantly in proximal muscles ( Kong et al, 2021 ; Ling et al., 2012 ; Ruiz et al., 2010 ) that reliably reflects the proximo-distal disease progression in patients with SMA ( Dubowitz, 2009 ). In contrast, the Taiwanese and Smn 2B/ - models exhibit only modest NMJ denervation ( Bowerman et al., 2012 ; Courtney et al, 2019b ; Lin et al., 2016 ). Moreover, while the degeneration and dysfunction of proprioceptive synapses onto motor neurons have been shown as one of the earliest pathological events in SMNΔ7 mice ( Fletcher et al., 2017 ; Mentis et al., 2011 ; Simon et al., 2019 ; Vukojicic et al., 2019 ), they have only been investigated at end-stage in the other two models ( Ackermann et al., 2013 ; Cervero et al., 2018 ; Hosseinibarkooie et al., 2016 ; Shorrock et al., 2018 ).…”
Section: Introductionmentioning
confidence: 89%
“…Recent studies have identified the P53 pathway as the likely culprit whose activation leads to the motor neuron degeneration in SMA [50,51]. Inhibiting the P53 pathway led to an almost complete rescue of motor neurons, but motor deficits, weight and survival were not rescued, highlighting that motor neuron loss is likely a late consequence of disease pathogenesis [51,52]. It is possible that it may simply not be present during a very mild disease course despite clinical motor dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular mechanisms evoking distinct spinal motoneuron death in SMA remain unresolved [127]. While the c-Jun N-terminal kinase (JNK)/c-jun signaling axis and the p53 signaling pathway have been implicated in severe SMA mouse models [128][129][130], the molecular mechanisms carrying out spinal motoneuron loss in SMA are likely complex, potentially context dependent, and may differ based on disease severity of the SMA model [131,132].…”
Section: Motoneuron Somasmentioning
confidence: 99%